Orientation strategies for a anthro-decentered terraformation (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
This article discusses the need to move beyond the context of the Anthropocene and de-center the human as an orienting strategy that situates us in the future of ecological thinking and aesthetic and technopolitical action. Specifically, it explores the potential of fictions of techno diversity shown from contemporary artistic practice, understood as a stimulating space for staging alternative futures of terraforming, which heterogeneously and inclusively imagine our coexistence with the non-human otherness.
Keywords: Orientation; terraforming; techno diversity; artistic practice; planetary thinking; fictions of the future